The development of new composite material for the grouting treatment of ordovician limestone aquifer and performance tests. (April 2015) - Li, S. C.; Li, Z. F.; Sha, F.; Liu, R. T.; Zhang, S. J.
Abstract : Fluidity and draining time of clay–coal waste rocks–cement aggregate composite grouting material were evaluated in this study. The characteristics of setting time and temperature, internal distribution of pore structure of the consolidation as well as impermeability, strength and softening coefficient were analysed. It was determined that the composition of the new composite material was clay 5–15%, coal waste rocks 45–60% and cement aggregate 20–50%. The permeability factor is <5·746×10 −7  m s −1, the softening coefficient is larger than 0·8, and it is capable for the treatment of limestone water with a pressure of up to 8 MPa.